THE IMPACT OF QUESTION BOARDS-ASSISTED TALKING STICK LEARNING MODEL ON GRADE IV ELEMENTARY SCHOOL STUDENTS MATHEMATICS LEARNING OUTCOMES - Alyani, Fitri; Rahmaniyanti, Rahmaniyanti (Prima: Jurnal Pendidikan Matematika, 2024)
Mathematics learning is the stage of transferring students' learning experiences in order to increase students' understanding so that they can gain competence related to the mathematics material being studied. The teacher's ability to design and carry out learning is a factor that can support success in learning procedure in order for pupils to become proficient in the subject. A cooperative learning model that uses talking sticks is one of the learning methods that can make the learning process more effective and efficient. The purpose of this study is to examine how fourth grade children at a Jakarta Public Elementary School learn mathematics using the talking stick learning model and a question board. Up to 60 fourth graders using the saturation sampling technique make up the population and sample in this study. The research method applied is quantitative in the form of experiments and the design chosen is a pseudo-experimental design. The instruments applied in this study consisted of talking sticks, question boards, and post-test sheets. The results of this study demonstrate a substantial relationship between grade IV students' mathematics learning outcomes and talking sticks as a learning approach supported by question boards in one of the Jakarta Public Elementary Schools.